2016
DOI: 10.1111/spol.12260
|View full text |Cite
|
Sign up to set email alerts
|

Narratives of Promise, Narratives of Caution: A Review of the Literature on Social Impact Bonds

Abstract: Social Impact Bonds (SIBs) are a new mechanism for delivering public services. This article reviews the emerging SIB literature in high‐income settings. It identifies three distinct narratives: a public sector reform narrative; a financial sector reform narrative; and a cautionary narrative. These are analyzed relative to three themes: public versus private values; outcomes contracting; and risk allocation. The first two narratives are complementary and offer a ‘win‐win’ portrayal of SIBs. The third narrative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
208
0
16

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 167 publications
(224 citation statements)
references
References 47 publications
0
208
0
16
Order By: Relevance
“…What's more, they are expected to enable greater accountability and deliver better outcomes than conventional forms of government purchasing, such as block contracting. Seen this way, SIBs can offer a "winwin" solution for all stakeholders, where socially minded investors can foster promising preventative interventions while providers receive the necessary funds to scale-up existing work, and government purchasers only pay for successful programming (Fraser et al 2018b). However, in practice, public services contracting is complex and there is limited evidence in support of paying entirely on outcomes from the performance-pay literature (Lagarde et al 2013).…”
Section: What Are Social Impact Bonds?mentioning
confidence: 99%
See 2 more Smart Citations
“…What's more, they are expected to enable greater accountability and deliver better outcomes than conventional forms of government purchasing, such as block contracting. Seen this way, SIBs can offer a "winwin" solution for all stakeholders, where socially minded investors can foster promising preventative interventions while providers receive the necessary funds to scale-up existing work, and government purchasers only pay for successful programming (Fraser et al 2018b). However, in practice, public services contracting is complex and there is limited evidence in support of paying entirely on outcomes from the performance-pay literature (Lagarde et al 2013).…”
Section: What Are Social Impact Bonds?mentioning
confidence: 99%
“…The traction SIBs have gained in policy circles also relates to their emergence in a difficult economic climate and is apparent in a recent literature review on SIBs in highincome settings that identified three emergent narratives (Fraser et al 2018b). The first narrative was a "public sector reform narrative" premised on the view that public, nonprofit and voluntary sector organisations have important shortcomings in terms of service design, delivery and accountability, that require private sector management techniques and values, such as financial incentives and "market discipline" to remedy these issues (Liebman 2011;Mulgan et al 2011).…”
Section: Why Do They Matter?mentioning
confidence: 99%
See 1 more Smart Citation
“…Research and scholarly debate about SIBs has mainly been conceptual so far (Fraser et al 2016). Empirical research has mostly been in the form of evaluation reports, with only a few academic studies (Arena et al 2016;Cooper et al 2016;Edmiston and Nicholls 2017) analysing existing SIBs with empirical methods.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical research has mostly been in the form of evaluation reports, with only a few academic studies (Arena et al 2016;Cooper et al 2016;Edmiston and Nicholls 2017) analysing existing SIBs with empirical methods. The conceptual arguments concerning SIBs have been following distinctive narratives (Fraser et al 2016): A public-sector-reform narrative located within broader theories of Public Management, a private-financial-sector-reform narrative located within broader theories of social entrepreneurship, and a cautionary narrative sceptical of new public management and social entrepreneurship.…”
Section: Introductionmentioning
confidence: 99%